Analisis Sistem Antrian pada Bank Negara Indonesia Kantor Cabang Kawasan Industri Medan - Paskah Riny Sirait; Parapat Gultom (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2023)
The problem that occurs at Bank Negara Indonesia of Medan Industrial Area Branch Office is the occurrence of unemployed tellers at certain hours. The purpose of this study is to determine the queue system at Bank Negara Indonesia of Medan Industrial Area Branch Office and to find out the optimal number of tellers at the bank. The structure of the queue model that occurs at Bank Negara Indonesia of The Medan Industrial Area Branch Office is a Multi Channel-Single Phase by applying the discipline of the First Come First Serve queue. The bank has 4 tellers with an average customer arrival value (λ) of 20 people per hour and an average service level (μ) of 22 people per hour. The results of data processing show the arrival pattern of Poisson-distributed customers and the general distribution service pattern. This study resulted in a queueing model (M / G / 4): (FCFS / ∞ / ∞). The optimal number of tellers in providing customer service is to reduce 1 teller. Based on the calculation results with only 3 tellers, it can reduce the probability of the teller being unemployed from the initial one by 40.25% to 39.97%.